Characteristics of starch-based pellets produced by hot-melt extrusion - Soares, Felipa Diaz-Argüelles y (2019)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014